The proposition - Hillcoat, John.; Pearce, Guy, 1967-; Winstone, Ray, 1957-; Huston, Danny, 1962-; First Look Home Entertainment (Los Angeles, CA : First Look Home Entertainment, 2006)
Charlie Burns is presented with an impossible proposition by local law enforcement. The only way for him to save his younger brother from the gallows is to dismiss his moral judgment and kill his psychotic older brother within nine days.
Title from container.
Originally released as a motion picture in 2005.
Special features: Director & writer commentary; 5 behind-the-scene featurettes; Previews; Deleted scenes; Photo gallery.
Guy Pearce, Ray Winstone, Danny Huston, John Hurt, David Wenham, Emily Watson.
MPAA rating: R; for strong grisly violence, and for language.
DVD, region 1; Dolby Digital.
Keywords: Brothers -- Australia -- Drama; Criminal behavior -- Australia -- Drama; Feature films; Western films; Thrillers (Motion pictures).; Video recordings for the hearing impaired